Single-Cell Profiles and Clinically Useful Properties of Human Mesenchymal Stem Cells of Adipose and Bone Marrow Origin. Issue 7 (June 2019) - Zhou, Wenyan; Lin, Junxin; Zhao, Kun; Jin, Kaixiu; He, Qiulin; Hu, Yejun; Feng, Gang; Cai, Youzhi; Xia, Chen; Liu, Hua; Shen, Weiliang; Hu, Xueqing; et al.
Background: Mesenchymal stem cells (MSCs) can be isolated from various tissues and can present themselves as a promising cell source for cell-based therapies. Although adipose- and bone marrow–derived mesenchymal stem cells have already been used in a considerable number of clinical trials for osteoarthritis treatment, systematic analyses from single- to bulk-cell resolution as well as clinical outcomes of these 2 MSCs are still insufficient. Purpose: To explore the characteristics and differences of adipose-derived stem cells (ADSCs) and bone marrow MSCs (BMSCs) at single- and bulk-cell levels, to study the clinical outcomes of these 2 cells on the treatment of osteoarthritis, and to provide potential guidance on the more precise clinical application of these MSCs. Study Design: Controlled laboratory study and meta-analysis. Methods: Same donor–derived ADSCs and BMSCs were isolated and cultured. Single- and bulk-cell assays were used to identify the characteristics of these 2 cells. Meta-analysis of clinical trials was done to compare the clinical therapeutic effects in osteoarthritis treatment with ADSCs and BMSCs. Results: Single-cell RNA sequencing analysis showed that the population of ADSCs showed lower transcriptomic heterogeneity when compared with BMSCs. Additionally, as compared with BMSCs, ADSCs were less dependent on mitochondrial respiration for energy production. Furthermore, ADSCs had a lower expression level of human leukocyte antigen class I antigen and higher immunosuppression capacity when compared with the BMSC population. Meta-analysis of current clinical trials of osteoarthritis treatment with MSCs consistently showed that ADSCs are more stable than BMSCs in their therapeutic effect. Conclusion: These results provide basic biological insights into human ADSCs and BMSCs at the single-cell resolution. Findings indicated that ADSCs may be a more controllable stem cell source, may be more adaptable to surviving in the hypoxic articular cavity niche, and may exhibit superiority in regulating inflammation. Based on the meta-analysis results of the different characteristics of ADSCs and BMSCs, ADSCs were implicated as being a better cell source for osteoarthritis treatment. Clinical Relevance: These results guide a more precise clinical application of adipose and bone marrow mesenchymal stem cells.